COMPARISON BETWEEN 2 ELEMENTARY SCHOOLS ABOUT BARRIERS IN ONLINE LEARNING FOR TEACHERS DURING PANDEMIC COVID-19 IN KEMILING DISTRICT BANDAR LAMPUNG CITY 2023 - Hasanah, Uswatun; Rilyani, Rilyani; Wandini, Riska (DIVERSITY Logic Journal Multidisciplinary, 2023)
Background. There are still many teachers who have learning barriers during the pandemic. Teachers from Elementary School 2 Beringin Raya and teachers from Elementary School 2 Sumberejo who had learning obstacles with students such as network constraints, learning applications, parental conditions, limited student learning devices because mobile phones were brought by working parents and lack of supervision. Research Purpose. To find out the comparison of online learning barriers for elementary school teachers during the Covid-19 pandemic at Elementary School 2 Beringin Raya and Elementary School 2 Sumberejo in Kemiling District, Bandar Lampung City. Research Method. Quantitative research with Cross-Sectional approach. The study was conducted on 73 respondents using total sampling technique.  Sampling technique using online learning barriers questionnaire during the Covid-19 pandemic. Findings. The hampered at Elementary School 2 Sumberejo is that the average score of 76.86 is higher (bad) than the average score at Elementary School 2 Beringin Raya is 71.16 lower (good). When compared using the statistical test Mann-Whitney test, there is also a difference in Mean Rank between Elementary School 2 Sumberejo 42.49 and Elementary School 2 Beringin Raya 31.66. There is a significant difference in value between Elementary School 2 Sumberejo and Elementary School 2 Beringin Raya with a p-value of 0.001. Conclusion. There is a difference in online learning barriers between the two elementary schools in Kemiling District, Bandar Lampung City in 2023. The teacher who was most hampered by learning during the Covid-19 pandemic was Elementary School 2 Sumberejo.